Diseminasi Edukasi Pencegahan Kejahatan Seksual di Dunia Maya Bagi Santri dan Wali Santri Yayasan Miftahun Najah, Desa Tobaih Barat, Kecamatan Sokobenah, Kabupaten Sampang - Aprilina Pawestri; Dewi Muti’ah; Ansori Ansori (Jurnal Masyarakat Mengabdi Nusantara, 2025)
The development of technology and information through new media, namely the “internet”, has an impact on unlimited social media relations. This development has implications for significant social, economic and or cultural changes in society so that it will have two consequences, namely negative impacts and positive impacts. Technological developments that have a negative impact will provide an obstacle to all sectors related to technology and information. This negative impact will lead to a crime in the internet world or better known as cyber crime. One of the most common cyber crimes is immoral crimes such as verbal harassment, content that violates decency. Such crimes have spread widely to various circles of society, including santri and santri guardians at the Miftahun Najah Foundation. This education includes understanding and awareness of applicable legal regulations related to internet use, ethics in interacting online, and steps to protect themselves from these threats. Through this dissemination, it is hoped that it can create smart, responsible, and protected online santri and santri guardians